Juvenile hormone III improves honeybee resistance to imidacloprid by protecting the midgut - Nana Wang; Kunrong Wang; Li Lei; Longtao Zhang; Xingqi Guo; Baohua Xu; Ying Wang; Chen Wang (Ecotoxicology and Environmental Safety)
Imidacloprid is one of the most commonly used insecticides and seriously threatens the survival of honeybees. Juvenile hormone III (JHIII), an important hormone in honeybees, plays a central role in the life cycle of honeybees; however, the mechanism by which JHIII responds to imidacloprid stress has not been determined. In this study, the resistance of Apis cerana cerana (Acc) to imidacloprid was greater than that of Apis mellifera (Am), and the application of JHIII significantly increased the resistance of both species of honeybees. RTqPCR revealed that two genes, juvenile hormone acid methyltransferase (JHAMT) and methyl farnesoate epoxidase (MFE), which are involved in JHIII biosynthesis, are key genes for improving resistance to imidacloprid via JHIII in honeybees. Silencing JHAMT and MFE with RNAi resulted in a lower content of JHIII in Acc and reduced resistance to imidacloprid. The exogenous application of JHIII compensated for the reduced resistance phenotype caused by gene silencing. Furthermore, histological examination of paraffin sections revealed that imidacloprid treatment caused loose intestinal cell arrangement, slight damage to columnar digestive cells and muscle cells, and chromatin condensation in basal layer cells. JHIII treatment reduced the degree of damage to the honeybee midgut cells and improved resistance to imidacloprid. The results of this study provide a new perspective and molecular basis for the study of the regulation of JHIII and the toxicity of imidacloprid in honeybees.